Twenty “must-read” research articles for primary care providers in Nunavik: scoping study and development of an information tool - Lemire, Mélanie; Cauchon, Michel; Paquin, Vincent; Fortin, Gabriel; Sandy, Glenda; Fletcher, Christopher; Perrault-Sullivan, Gentiane; Ouellet, Jean (International Journal of Circumpolar Health, 2020)
While health needs in Nunavik are distinct, there is a scarcity of knowledge transfer intended forlocal primary care providers. We aimed to build an information tool in the form of a newsletterand a website to share with them a selection of relevant research articles. To identify sucharticles, a scoping study of Inuit health research published between 2012 and 2017 was con-ducted. Selection criteria were adapted from the framework of information mastery. After adatabase search yielding 2896 results, publications were screened for eligibility. Next, the 226eligible articles were evaluated and scored for their relevance, their methods (including commu-nity participation), their local applicability and their clinical utility. The 20 highest-scored articleswere selected for dissemination in a newsletter. They were summarised and presented in 6thematic emails: Child Development, Infectious Diseases, Traditional and Modern Medicine,Metabolism, Nutrition and Contaminants, and Inuit Perspectives. The newsletter was sent toover 190 health workers and regional stakeholders in Nunavik and was also published online.We hope that this project will foster knowledge sharing and inter-sectorial collaboration betweenresearch, public health and clinical care. Trends in Inuit health research are discussed.